Changes in the structure of lymphatic nodes under the effect of monosodium glutamat and correction - Harapko , T.V.; Kochmar , M.Yu.; Popovych , F.A.; Rosola , T.F.; Foros , A.I.; Yatsko , S.I.; Zavadska , M.B. (Морфологія / Morphologia / Morfologìâ, 2023)
Background. The use of food additives in the food industry is widespread, but their effect on the organs of the lymphoid system has not been studied enough. The purpose of the study was to study the changes in the structure of the parenchyma of the lymph nodes of rats under the conditions of the action of monosodium glutamate and correction with melatonin. Methods. The study was conducted on 42 white male and female rats of reproductive age. Experimental animals were on a high-calorie diet for six weeks (first group), followed by two weeks of melatonin correction (second group). A high-calorie diet was achieved by adding monosodium glutamate to the diet of animals at a dose of 0.07 g/kg of rat body weight. The dose of melatonin was 10 mg/kg of rat body weight. Results. It was investigated that after six weeks of exposure to monosodium glutamate, destructive and degenerative changes occur, in particular, in the parenchyma of the nodes, there are many lymphocytes at various stages of apoptosis, many macrophages, the cytoplasm of which contains numerous phagosomes, primary and secondary lysosomes, fragments of damaged lymphocytes, and other osmiophilic inclusions. It was found that after six weeks of exposure to monosodium glutamate followed by two weeks of melatonin, the relative area of the cortical substance of the node, lymphoid nodules, and mantle zone increases, but remains significantly smaller than that of the intact group of animals. The number of secondary lymphoid follicles decreases, the intercellular space is expanded, there are signs of perivascular edema, a large number of osmiophilic inclusions. Conclusion. After six weeks of exposure to monosodium glutamate followed by two weeks of melatonin, structural changes in mesenteric lymph nodes were less pronounced than in the group of animals that received monosodium glutamate for six weeks.